2023
DOI: 10.3390/app13084959
|View full text |Cite
|
Sign up to set email alerts
|

Boron Carbonitride Films with Tunable Composition: LPCVD and PECVD Synthesis Using Trimethylamine Borane and Nitrogen Mixture and Characterization

Abstract: This study reports the chemical vapor deposition of amorphous boron carbonitride films on Si(100) and SiO2 substrates using a trimethylamine borane and nitrogen mixture. BCxNy films with different compositions were produced via variations in substrate temperature and type of gas-phase activation. The low-pressure chemical vapor deposition (LPCVD) and plasma-enhanced chemical vapor deposition (PECVD) methods were used. The “elemental composition—chemical bonding state—properties” relationship of synthesized BCx… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 104 publications
0
2
0
Order By: Relevance
“…For N 1s peaks (Figure 3d), which can also be divided into two peaks corresponding to NÀ B (397.7 eV) and NÀ C (398.3 eV). [14,16] The B: C: N atomic ratio calculated from the XPS spectra is about 6.5: 1: 5.8.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For N 1s peaks (Figure 3d), which can also be divided into two peaks corresponding to NÀ B (397.7 eV) and NÀ C (398.3 eV). [14,16] The B: C: N atomic ratio calculated from the XPS spectra is about 6.5: 1: 5.8.…”
Section: Resultsmentioning
confidence: 99%
“…Theoretical calculations also have revealed that the electronic and optical properties of ternary BÀ CÀ N nanostructures can be tailored by changing its composition, which show great potential applications in optoelectronics device, supercapacitors, and catalyst. [8] Several methods have been reported for the synthesis one-dimensional (1D) BÀ CÀ N nanotubes (BÀ CÀ NNTs) and 2D BÀ CÀ N nanosheets (BÀ CÀ NNSs), [9][10][11][12][13][14][15][16][17][18] However, B doping and N doping have a very low efficiency by boric acid and N-containing compounds due to their poor reactivity. Thus, the BÀ CÀ N micro-nano structures with regular morphology prepared by these methods either suffer from low yield and/or low purity, which would greatly limit the application of BÀ CÀ N nanomaterials.…”
Section: Introductionmentioning
confidence: 99%